Poly (N, N-dimethyl aniline) Coating for Stainless Steel, Synthesis, Characterization and Corrosion Protection in Sea Water 3.5% NaCl Solution - A. Alshanwi, Naema; A. Alsammaraie, Sahar (Iraqi Journal of Science, 2023)
This research involves the synthesis of conductive polymer includes: poly (N, Ndimethylaniline) on metal surface which is stainless steel 316 by usingelectrochemical polymerization technique. Parameters of this research are voltagerang, scan rate, number of cycles. The tests for corrosion protection of the polymercoated and uncoated stainless steel substrate was investigated in artificial sea waterof 3.5% NaCl solution by tafel and potentiodynamic procedures. Fourier TransformInfrared Spectroscopy (FTIR), UV-Visible absorption spectroscopy, ScanningElectron Microscope (SEM) and Atomic Force Microscope (AFM) were used todiagnose and describe the structure and morphology of the coating. Parameters ofcorrosion are: corrosion current Icorr, corrosion potential Ecorr, protection efficiency(PE %), polarization resistance (Rp) and the effect of different temperatures range(293 to 323) K in the inhibition efficiency of coated and uncoated stainless steelsurface. Change in the free, enthalpy and entropy have been determined. Apparentenergies of activation have been calculated for the corrosion process from thecorrosion rates and Arrhenius plots. This results of corrosion test showed that Poly(N, N-dimethyl aniline) ensure chemically stable, environmentally viable and havegood corrosion protection of stainless steel in artificial sea water of 3.5% NaClsolution.